SERVICE PER CONCEPTION PADA SAPI PERAH LAKTASI DI BALAI BESAR PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BBPTU-HPT) BATURRADEN PURWOKERTO JAWA TENGAH - Rahmadhanil Putra Rusadi; Madi Hartono; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of this research was to determine the level of S/C and the factors value that affect the level of S/C atlactating dairy cattle in BBPTU-HPT Baturraden Purwokerto Central Java, onApril, 29 th – May 13 th 2014.This research used sensus method with primary and secondary data. Analysis data used regression analysiswith SPSS (Statistics Packet for Social Science) program.The result showed that the S/C at BBPTU-HPT Baturraden is 2,12±1,23. Factors affecting the value of S/Cform the herds man and the cattles. On the level of cattle are the education of herds man that negativelyassociated with factor value 0,615, number of the cattle that positively assosiated with factor value 0,067,herdsman knowledge that positively assosiated with factor value 0,721 and the distance between the cowshedwith office that negatively assosiated with factor value 0,060. Factor affecting the S/C on dairy cattle arelactation level that positively assosiated with factor value 0,174, days open that assosiated withfactor value 0,238, mating post partus that negatively assosiated with factor value 0,214, calving intervalthat negatively assosiated with factor value 0,326, lactating duration that positively assosiated with factorvalue 0,278 and dry period that positively assosiated with factor value 0,343.